Penerapan Pendidikan Karakter dan Kritis dalam Social Project Mahasiswa PGSD di Panti Asuhan Blitar. - Khoirul Wafa; Icha Manisha Putri Saifdayu; Siti Laelatul Mab'ruroh; Cahya Alifia Mawadati; Yulia Rizki Sania (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This social project aims to instill character values and develop critical thinking skills among children at Insan Madani Orphanage, Blitar Regency. The program was designed as a form of community service by PGSD students of Nahdlatul Ulama University Blitar through an educational, interactive, and practical approach. Activities included seminars, discussions, educational games, poster-making, and hands-on projects such as planting vegetables. The method emphasized participatory learning to foster values such as responsibility, cooperation, and empathy, while simultaneously training logical, analytical, and reflective thinking skills. The results showed high enthusiasm and active participation from the children in each session. They were able to express ideas confidently and demonstrated improvement in understanding character concepts and critical thinking. The orphanage welcomed the program and expressed hope for future collaboration. For the students, this activity provided real-world experience in applying character education and nurturing social awareness. This program demonstrates that the synergy between character development and critical thinking training is essential to shaping a golden generation that is intellectually capable and morally grounded.